Charlotte's web (London Puffin, 1993)
This is the story of a girl called Fern who loves a little pig called Wilbur. And of how Wilbur's dear friend Charlotte A. Cavatica, a beautiful grey spider, saves Wilbur from the unusual fate of nice fat pigs, by a wonderfully clever plan (which no o ne else could possibly have thought of).
Keywords: Animals -- Fiction; Spiders -- Fiction; Swine -- Fiction; English fiction -- Children's stories; United States